(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
An extremely uncommon tooth developmental anomaly seen such as bilateral primary mandibular first molar with a single root and single canal. Various researchers found that due to failure of invagination of HERS leads to various anomalies in root morphology. A 9 year old girl with pain on lower left side of the jaw originated from mandibular left first molar. On right side there was also presence of 84 with single root. The tooth was treated by pulpectomy followed by restoration. Due to unusual morphology, the chance of endodontic mishaps is extremely high in the search of additional canal, which can be overcome by proper knowledge of root morphology and radiographic interpretation. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 67-71